Performance of Exporters: Scale Effects or Continuous Productivity Improvements - Crt Kostevc (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2005)
Following along the lines of a growing literature on the causal link between exporting and productivity this paper analyzes the existence of 'learning-by-exporting'in Slovenian manufacturing between 1994 and 2002. This paper asks whether in addition to good firms self-selecting into exports and multinational production exporting (multinational production) further improves their perfirmance compared with non-exporters. I develop a simple model of trade and international production with heterogeneous firms that generates learning effects through competition in the export markets. The estimations perfirmed on the Slovenian sample indicate that more productive firms tend to self-select into more competitive markets, while there is no conclusive evidence of learning-by-exporting. Namely, although new exporters experienced a surge in productivity in the initial year of exports the effect dissipates in the following years. This leads me to conclude that the perceived learning effects are in fact only a consequence of more efficient utilization of available production capacity brought forth by the opening of an additional market.
Keywords: D24; F12; F14; 330; Firm heterogeneity; exports; multinational firm; learning-by-exporting; difference-in-differences; martching; Export; Produktivität; Multinationales Unternehmen; Theorie; Schätzung; Slowenien